Characteristics and health effects of particulate matter emitted from a waste sorting plant. (1st August 2022) - Barkhordari, Abdullah; I. Guzman, Marcelo; Ebrahimzadeh, Gholamreza; Sorooshian, Armin; Delikhoon, Mahdieh; Jamshidi Rastani, Mehdi; Golbaz, Somayeh; Fazlzadeh, Mehdi; Nabizadeh, Ramin; Norouzian Baghani, Abbas
Graphical abstract: Highlights: Particulate matter (PM) emitted from waste sorting plant (WSP) were studied. Health risks to plant workers regarding exposure to PM were quantified. The ratio of indoor PM to outdoor PM (I/O PM) ranged from 0.8 to 46.3. LTCRs for PM via inhalation exposure route ranged from 3.41 × 10 −6 to 9.43 × 10 −5 . Exposure to PM2.5 and PM10 in the WSP lead to possible risk. Abstract: Solid waste components can be recycled in waste paper and cardboard sorting plants (WPCSP) through a multistep process. This work collected 15 samples every six days from each of the 9 points selected to study the processes taking place in a WPCSP (135 particulate matter samples total). Examining the concentration and size fraction of particulate matter (i.e., PM1, PM2.5 and PM10 ) in WPCSP is an essential issue to notify policy makers about the health impacts on exposed workers. The major activities for increasing of the concentration of PM in various processing units in the WPCSP, especially in hand-picking routes I and II were related to manual dismantling, mechanical grinding, mechanical agitation, and separation and movement of waste. The results of this work showed that a negative correlation between temperature and particulate matter size followed the order PM10 > PM2.5 > PM1 . Exposure to PM2.5 and PM10 in the WPCSP lead to possible risk (HI = 5.561 and LTCRs = 3.41 × 10 −6 to 9.43 × 10 −5 for PM2.5 and HI = 7.454 for PM10 ). The exposure duration and the previous concentrations had the most effect on the ILCRs and HQs for PM2.5 and PM10 in all sampling sites. Hence, because WPCSP are infected indoor environments (I/O ratio > 1), the use of control methods such as isolation of units, misting systems, blower systems equipped with bag houses, protective equipment, a mechanical ventilation system, and additional natural ventilation can reduce the amount of suspended PM, enhance worker safety, and increase the recycling rate.